Yeast protein as a fishmeal substitute: impacts on reproductive performance, immune responses, and gut microbiota in two sow hybrids - Zhou, Pan; Liu, Qi; Zhao, Yang; Wu, Yachao; Shen, Jianbo; Duan, Tao; Che, Long; Zhang, Yong; Yan, Honglin (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe persistent African swine fever epidemic has significantly compromised China’s swine production. To accelerate production recovery, commercial farms are increasingly adopting retention of two-way backcross sows (Landrace × Yorkshire × Landrace, LLY) for breeding. This study aimed to investigate the effects of yeast protein, an emerging sustainable protein source, on reproductive performance, immune responses, and gut microbiota in two-way crossbred sows (Landrace × Yorkshire, LY) and LLY sows.MethodsThe experiment employed a 2×2 factorial design evaluating two fixed factors: sow hybrid (LY vs LLY) and yeast protein supplementation (0% vs 2.6%). The four treatment groups were: LY sows without yeast protein supplementation (LY-C), LLY sows without yeast protein supplementation (LLY-C), LY sows with yeast protein supplementation (LY-YP), and LLY sows with yeast protein supplementation (LLY-YP). A total of one hundred healthy sows of 2-6 parities (50 LY sows and 50 LLY sows), were stratified by backfat thickness, body weight, and parity, then randomly allocated to the four treatment groups on day 105 of gestation, with 25 sows in each group. The experimental period lasted from day 106 of gestation to day 18 of lactation.Results and conclusionYeast protein supplementation showed no significant effects on most reproductive parameters of different sow hybrids, but reduced backfat loss by 30.5% during lactation (P < 0.05) and demonstrated a numerical reduction in mummification rate of fetuses (P = 0.06). Immunological assessments revealed that LLY sows exhibited 26.8% lower serum IgM concentration than LY sows (P < 0.05), while yeast protein supplementation significantly reduced serum IL-1β levels by 45.6% (P < 0.05) on day 18 of lactation. 16S rRNA gene sequencing analysis revealed comparable fecal microbial diversity across treatments (P > 0.05), though differences were observed in certain bacterial genera between LY and LLY sows during late gestation and lactation. Yeast protein supplementation enriched beneficial bacteria including Ruminococcaceae_UCG-002, Rikenellaceae_RC9_gut_group, and Christensenellaceae_R_7_group, while suppressing potentially detrimental bacteria such as Family_XIII_AD3011_group (P < 0.05). These findings demonstrate the practical feasibility of retaining LLY sows for commercial breeding. Yeast protein supplementation, as a substitute for fishmeal during late gestation and lactation, significantly reduced lactational backfat loss, moderately attenuated inflammatory response, and enhanced gut microbiome homeostasis through selective microbial enrichment in sows.